Effect of micellar structure of casein and its modification on plasmin-induced hydrolysis. (December 2017) - Bhatt, H.; Cucheval, A.; Coker, C.; Patel, H.; Carr, A.; Bennett, R.
Abstract: Plasmin-induced hydrolysis of casein in milk can lead to many defects including proteolysis, age gelation, and bitterness. The susceptibility of casein to plasmin can be affected by micellar structure and modification of the lysine residues on caseins. Different levels of casein modification and dissociation of the casein micelle structure were achieved through succinylation. Succinylation occurred at residues Lys7, Lys34, Lys36, Lys42, Lys83 and Lys124 in αS1 -casein; Lys80, Lys150, Lys152, Lys158 and Lys165 in αS2 -casein; Lys28, Lys29, Lys32, Lys99, Lys105, Lys107 and Lys113 in β-casein, as identified using liquid chromatography–tandem mass spectrometry. The dissociation of caseins from the casein micelle reduced steric hindrance and made the protein more readily susceptible to hydrolysis by plasmin. However, the formation of succinyl-lysine rendered β-casein unrecognisable to the substrate-binding pocket of plasmin, resulting in a non-linear decrease in level of hydrolysis because of the competitive effect of micelle dissociation.